RANCANG BANGUN PENGELOMPOKAN BAKAT KEMAMPUAN BEKERJA BERBASIS DEKSTOP PADA TELKOMSIGMA JAKARTA - Jully Triansyah; Dicky Rodika Aji (Jurnal Informatika, 2021)
Abstract : With the existence of highly advanced information technology as it is today, it is certainly very helpful for human work in creating, changing and seeking information. The process of searching for information at Telkomsigma Jakarta still uses a system that is not well computed. In designing this talent grouping application, the author uses the C # language as a language to compile logic and uses visual studio as an application to display C # language logic lines and acts as an IDE so that the logic lines that have been compiled can be processed into an application, and use devexpress as an additional application for visual studio which contains controls that can help to create an application.The method used in developing this system uses the Extreme Programming method, while the methods for collecting the funds use observation, interviews and literature study.By utilizing this work ability grouping application, it makes it easier for users to map the information needed about the ability of each employee to work. Keyword : Ability, C#, DevExpress, Extreme Programming, IDE